P01.072 Hydroxychloroquine and short course radiotherapy for elderly patients with glioma: a randomised study. (19th September 2018) - Brazil, L; Swampillai, A; Mak, K; Hackshaw, A; Edwards, D; Mesiri, P; Clifton-Hadley, L; Shaffer, R; Lewis, J; Watts, C; Gkogkou, P; Chalmers, A; et al.
Abstract: Background: Treating elderly patients with glioblastoma remains challenging and alternatives to conventional cytotoxics, particularly in patients with unmethylated tumours are required. Pre-clinical data suggest that autophagy inhibition sensitizes gliomas to radiotherapy and chemotherapy Material and Methods: We conducted an open-label multicentre randomized phase-II study of patients aged >=70, performance status 0–1 with newly diagnosed high-grade glioma considered suitable for short course radiotherapy. They were randomized (1:2) to a calibration arm given radiotherapy (RT) alone (30Gy;5Gy/6fractions over 2 weeks), or an experimental arm given RT plus hydroxychloroquine (HCQ, 200mg orally twice daily) from 7 days prior to RT until progression/toxicity. The primary endpoint was one-year overall survival (OS; target 34%). Secondary endpoints included progression free survival (PFS), quality of life and toxicity. Results: Fifty-three patients with median age 75 were included May 2013 to Oct 2016 (n=35 RT+HCQ, n=18 RT alone). One-year survival was 20.3% (95%CI 8–36) in the experimental arm and median OS was 7.9 months. In the calibration arm, one-year survival was 47.6% (95%CI 2–71) and median OS was 11.8 months. Six-month PFS was 25.2% vs 36.5%. Grade 3–5 toxicities occurred in 60% (RT+HCQ) and 38.8% (RT alone), which was not significantly different, with no obvious imbalance in specific events. Common toxicities included lethargy and pulmonary infections. QoL did not differ between arms. The Data Monitoring Committee stopped recruitment early because the experimental arm could not reach its target 1-year OS Conclusion: Despite growing interest in autophagy inhibition as a potential mechanism for treating cancer, giving HCQ with short course radiotherapy did not improve outcomes compared to radiotherapy alone. Although median OS was similar to data from other studies for this patient group, it was worse than the calibration arm. Future opportunities could include using higher doses of HCQ, or definition of selective biomarkers for response to autophagy inhibition.